Development of Kirkwood-Buff derived force field for phospholipids - Gajaweera, Sandun (Kansas State University, 2021)
Recently, we have developed an improved force field for the simulation of peptides and proteins. To develop accurate models for lipids, we present force field parameters for the study of 8 glycerophospho lipids in water. The force field parameters for the polar groups of lipids (head groups, glycerol, ester functionalities) were developed to reproduce the experimental Kirkwood-Buff (KB) integrals for small molecule analogs and their mixtures with water. This is not possible for the hydrocarbon tails or the lipids. Consequently, a more traditional approach was used to ensure that a variety of common properties of lipid membranes were reasonably reproduced. The electron density profiles, the area and volume per lipid, the lipid lateral diffusion rates, and the hydrocarbon chain order parameters, were investigated and compared with experimental data where available.
Keywords: Lipids; Molecular dynamics simulations